The Effectiveness of PBL Model with STEAM Approach Assisted by Android Application on Students' Mathematical Problem Solving Ability - Akbar, Faisal Hibatullah; Rahayu, Ratri; Wanabuliandari, Savitri (Journal of Education Technology, 2022)
The mathematical problem solving ability of class XI students at an islamic senior high school is still low. Based on the results of the initial test which was attended by 181 students, only 16,02% of students completed the KKM, while 83,98% had not. Therefore, study aims to analyses the effectiveness of PBL learning model with STEAM appr oach assisted by android application. The design of this study was quasi-experimental with a posttest-only control group design. Class XI MIPA 7 as the experimental class and class XI MIPA 2 as the control class. The data consists of tests and documentation. The test instrument is the posttest in the form of an essay. Data analysis used t-test and z-test. The results show that PBL with the STEAM approach assisted by an android application is effective in improving the mathematical problem solving abilities of class XI students on the material of sequences and series. Further research on the PBL model with the STEAM approach assisted by android applications still needs to be done, so that its application can be in accordance with the times.